2020
DOI: 10.1111/gcb.15160
|View full text |Cite
|
Sign up to set email alerts
|

Global ecosystems and fire: Multi‐model assessment of fire‐induced tree‐cover and carbon storage reduction

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 75 publications
3
65
1
Order By: Relevance
“…2b). This effect of fire has also been shown by Lasslop et al [42]. Nonetheless, the impact of fire on the decrease and increase biomass was small in the impact and recovery phase.…”
Section: The Hysteresis Of the Tropical Forestsupporting
confidence: 80%
See 1 more Smart Citation
“…2b). This effect of fire has also been shown by Lasslop et al [42]. Nonetheless, the impact of fire on the decrease and increase biomass was small in the impact and recovery phase.…”
Section: The Hysteresis Of the Tropical Forestsupporting
confidence: 80%
“…Previous studies suggest temperature stress on the vegetation as the cause for this large reduction [41]. Without fire, the total biomass was ca 25% larger, due to missing combustion and fire-related tree mortality [42]. In the recovery phase, atmospheric CO 2 decreased over another 350 years, until the starting value of 284 ppm was reached.…”
Section: Trajectories Of Tropical Biomass and Temperaturementioning
confidence: 93%
“…The results showed that our model performed well in simulating most land variables (more details can be accessed from Note S3). In addition, noting that fire has an important effect on vegetation distribution 86,87 , we evaluated our simulated ''offline'' present-day global vegetation distribution (i.e., with fire included) by comparing it with the European Space Agency's Land Cover Climate Change Initiative dataset 47 (Note S3).…”
Section: Model Validationmentioning
confidence: 99%
“…In this study, a process-based fire model of intermediate complexity has been implemented in the SSiB4/TRIFFID, called SSiB4/TRIFFID-Fire. The fire model developed by Li et al (2012Li et al ( , 2013 was first built on the model platform of CLM-DGVM and has been incorporated in IAP-DGVM (Zeng et al, 2014), CLM4.5 (Oleson et al, 2013, CLM5 (Lawrence et al, 2019), LM3 in Earth system model GFDL-ESM (Rabin et al, 2018;Ward et al, 2018), AVIM in Climate System Model BCC-CSM (Weiping Li, personal communication, 2016), E3SM Land Model (ELM; Ricciuto et al, 2018), NASA GEOS catchment-CN4.5 model (Zeng et al, 2019), and DLEM (Yang et al, 2014), and it has been partly used in GLASS-CTEM (Melton and Arora, 2016). The following briefly describes the fire schemes adapted from Li et al (2012, , and our own modifications.…”
Section: Fire Model and Modificationsmentioning
confidence: 99%